Factor the fallowing quadratic equation :f(x)=x^2-5x-6. Then verify the answer in a graph if possible.

A. (x+1)(x+6)
B. (x-1)(x-6)
C. (x+1) (x-6)
D. (x-1)(x+6)

1 answer

To factor the quadratic equation \( f(x) = x^2 - 5x - 6 \), we need to find two numbers that multiply to \(-6\) (the constant term) and add up to \(-5\) (the coefficient of the linear term \(x\)).

The two numbers that satisfy these conditions are \(-6\) and \(1\), since:

  • \(-6 \cdot 1 = -6\)
  • \(-6 + 1 = -5\)

Thus, we can write the factored form of the quadratic as: \[ f(x) = (x - 6)(x + 1) \]

This corresponds to option C: \((x + 1)(x - 6)\).

Verification through Expansion

To verify the factorization, we can expand \((x + 1)(x - 6)\): \[ (x + 1)(x - 6) = x^2 - 6x + 1x - 6 = x^2 - 5x - 6 \] This confirms that the factorization is correct.

Graph Verification

To verify graphically, you can plot the function \(f(x) = x^2 - 5x - 6\) and observe the points where the graph intersects the x-axis (the roots). The roots of the quadratic based on our factorization are \(x = 6\) and \(x = -1\).

In practice, you could use graphing software or a graphing calculator. Here's a brief description of how you could visualize it:

  1. Create the graph for \(y = x^2 - 5x - 6\).
  2. Look for the points where the graph intersects the x-axis at \(x = 6\) and \(x = -1\).
  3. Confirm that these points correspond to the factors found.

Conclusion

The correct factored form is \((x + 1)(x - 6)\), which is option C.